Cholesterol induces cardiac hypertrophy by activating the AKT pathway - Lee, Hyunjung; Yoo, Young Sook; Lee, Daekee; Song, Eun Joo (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Cardiac hypertrophy leads to decompensated heart function, predisposition to heart failure, and sudden death due to physiological and pathological stimuli. Although high cholesterol is considered a principal risk factor for atherosclerosis and heart disease, it has not been shown whether cholesterol itself is sufficient to cause cardiac hypertrophy. In this study, we investigated whether cholesterol induces cardiac hypertrophy, and identified cellular mechanisms underlying hypertrophic responses using H9c2 cells as a model system. Here we show that cholesterol loading significantly increased the cellular surface area and upregulated hypertrophy marker gene, beta-myosin-heavy chain (beta-MHC). Cholesterol loading alone activated the extracellular signal-regulated kinase (ERK)/mitogen activated protein kinase (MAPK) and phosphatidylinositol-3-kinase (PI3K)/AKT pathways. Conversely, cholesterol induced hypertrophic characteristic features such as increase in cellular surface area, and the expression of beta-MHC mRNA is markedly inhibited by LY294002, a PI3K kinase inhibitor. These results suggest that cholesterol may play a key role in the development of cardiac hypertrophy through the activation of the PI3K/AKT pathway activation. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: GENE-EXPRESSION; HEART-FAILURE; IN-VIVO; CELL